Educational Psychology / Fourth Edition - Santrock John W (Mcgraw Hill Book Company, 2009)
Behind every famous person is a fabulous teacher. Educational Psychology: A Tool for Effective Teaching, Cognitive and Language Development, Social Contexts and Socioemotional Development, Individual Variations, Sociocultural Diversity, Learners Who Are Exceptional, Behavioral and Social Cognitive Approaches, The Information-Processing Approach, Complex Cognitive Processes, Social Constructivist Approaches, Learning and Cognition in the Content Areas, Planning and Instruction and Technology, Motivation and Teaching and Learning, Managing the Classroom, Standardized Tests and Teaching, Classroom Assessment.